PELAKSANAAN ASESMEN KESIAPAN SEKOLAH PADA ANAK DI KB/TK BUNGA BANGSA - Melina Lestari; Maria Oktasari (Jurnal PkM Pengabdian kepada Masyarakat, 2022)
Children are valuable assets as a future for the betterment of a nation. For that, special attention is needed in terms of optimizing the development of children. This effort is done through education in school. However, the development of each child is different, including in terms of school readiness. For this reason, assessment of school readiness in early childhood is important to do. School readiness assessments are carried out face-to-face limited. Instruments are given in the form of intelligent tests and observations of aspects of development. Based on the assessment results that have been done, in general learners are ready to nail level to kindergarten B and elementary school level, but there are some learners who need parental help to optimize the physical aspects of motor, cognitive, social, emotional and moral so that learners can be better prepared to enter the school world. Recommendations for the school should be made at the beginning of the year, mid and end of the school year so that the results can describe the child's development more deeply.